A Study among Community Living Underneath SUTET about The General Health Condition and The Electromagnetic Fields Exposures - Wawolumaya, Corrie; Darwanto, Djoko (UI Scholars Hub, 2009)
Jaringan SUTET Perusahaan Listrik Negara banyak melalui daerah pemukiman. Tujuan penelitian mendapatkan gambaran kesehatan penduduk yang bermukim di bawah SUTET dan di daerah urban miskin Jakarta dan sekitarnya. Penelitian disain kroseksional ini dilakukan pada sample 1200 kepala keluarga yang ditarik secara stratifikasi proportional purposif berdasarkan zona kuat medan elektromagnet. Data dikumpulkan dengan metoda observasi, wawancara dan pemeriksaan kesehatan. Kuat medan listrik dan medan magnet diukur terpisah di luar rumah, dan di dalam rumah. Ditemukan kuat medan listrik tertinggi pada ketinggian 1 meter di atas tanah 3,1 kV/m. Kuat medan magnet 550 mA/m atau 687,5.10-3µT diidentifikasi dalam zona 1 0-20 m yang menurun berangsur pada zona 2 300mA/m dan mendekati 0 pada zona 3. Medan listrik dan medan magnet berada di bawah nilai ambang SNI 2003, 5 kV/m dan 0,1 mT atau 80.104 mA/m (note: 1 A/m = 1,25 µT). Medan listrik tertinggi ditemukan pada ketinggian 1 meter dari tanah 2,5 kV/m pada jam 02.00–03.00 pagi dan medan magnet ttinggi 2400 mA/m pada jam 12.00-16.00 .Jenis rumah terbanyak adalah rumah kumuh ( 30 %) telah dimukimi lebih 30 tahun. Penyakit utama di semua zona adalah gangguan gigi geligi, myopia dan hipertensi yang tidak berbeda antara zona. SUTET or the Extra High Voltage Transmission Line of 500 kV has passed through larger residential areas in the community. The aim of study is to provide the description of general health condition of community residing under SUTET in the urban poor of Jakarta and surrounding. The design of study was cross sectional, carried out among 1200 respondents which were taken stratified proportional purposively, based on zones of the electromagnetic field exposures. Data were collected through observation, interview and physical examination. The electric field and the magnetic field exposures were separately measured outside and inside the houses. The highest electromagnetic field exposures were measured at one meter height above the ground , for the electric field 3,1 kV/m. and the magnetic field 550 mA/m or 687,5.10-3µT, were identified in zone 1 0-20 ms. The magnetic field was decreasing gradually through zone 2 300mA/m and nearing zero in zone 3. Both the highest electric field and the magnetic field exposures were below the threshold values stated by SNI 2003, 5 kV/m dan 0,1 mT or 80.104 mA/m (note: 1 A/m = 1,25 µT). The highest electric field exposure was identified at one meter height from the ground 2,5 kV/m at 02.00–03.00 hours a.m and the highest magnetic field 2400 mA/m at 12.00-16.00 hours p.m. The biggest portion of houses was poor ( 30 %) were being housed for morethan 30 years. The major diseases were found similar in all zones i.e., dental diseases, myopia and hypertension.